WORDS IN ENGLISH WHICH ARE NOT ENGLISH WORDS ORIGINALLY - Samad Yuldoshev (Western European Studies, 2025)
All languages in the world enrich their vocabulary by borrowing words from foreign languages, in addition to their own lexicon. This increases the vitality of the language and keeps it updated
Keywords: addition; languages; vocabulary